2022
DOI: 10.1029/2021gl097446
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Sources and Transport for Extreme Precipitation Over Henan in July 2021

Abstract: Frequent extreme precipitation events have resulted in severe disasters to agriculture, the economy, and human health in recent decades. Widespread concerns about extreme precipitation have been aroused among the public, the government, and the research community. Researchers have conducted numerous studies on the mechanisms responsible for extreme precipitation events (Agel et al., 2018;Collow et al., 2016). Favorable local dynamic conditions (ascending motion) and instability are critical for the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 38 publications
(48 reference statements)
4
51
0
Order By: Relevance
“…Noting that the endpoints of trajectories that belongs to the west cluster are concentrated in the southern area of China. Recently, Nie and Sun (2022) demonstrated that such moisture sources are caused by local terrestrial water recycling and highlighted its important role that contributing to the formation of the “21.7” heavy rainfall event in Henan Province. In our opinion, we would rather believe such a moisture source comes from the south‐westerly monsoon flow.…”
Section: Resultsmentioning
confidence: 99%
“…Noting that the endpoints of trajectories that belongs to the west cluster are concentrated in the southern area of China. Recently, Nie and Sun (2022) demonstrated that such moisture sources are caused by local terrestrial water recycling and highlighted its important role that contributing to the formation of the “21.7” heavy rainfall event in Henan Province. In our opinion, we would rather believe such a moisture source comes from the south‐westerly monsoon flow.…”
Section: Resultsmentioning
confidence: 99%
“…This is limited by current ocean circulation models, which focus on the storm surge and neglect precipitation that falls directly into the simulation domain and the interaction between rainfall-runoff and storm surge. Ignoring these precipitation amounts may result in underestimating the compound flood in rive deltas, especially during slow-moving storms which dump an excessive amount of precipitation over a long period of time, such as Hurricane Harvey (2017) (Zhang et al, 2018), Florence (2018) (Ye et al, 2021), Ida (2021) (Flowers, 2021), and super Typhoon In-fa (2021) (Nie & Sun, 2022). Meanwhile, due to the adoption of simplified flow representation (Bates et al, 2005), hydrologic/hydrodynamic models are not feasible to simulate hydrodynamics in deep water, for example, astronomical tides, storm surges, and wind waves in offshore areas.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the WPSH is associated with ocean signals such as ENSO and the Pacific Decadal Oscillation [66][67][68], which, depending on their phase, can affect the formation pattern of TCs. In addition, large-scale circulation can transport moisture from TCs and interact with high-latitude weather systems, resulting in remote rainfall from TCs and extreme rainfall locally, such as the extreme rainfall events in July 2021 in Henan-one of the most populated provinces in China [69,70].…”
Section: Discussionmentioning
confidence: 99%